Influence of Self-Efficacy, Physical Work Environment, and Internal Communication on Job Satisfaction of Non-Production Employees PT Poliplas Makmur Santosa Ungaran - Savina Umi Lestari; Rara Ririn Budi Utaminingtyas; Isnaini Nurkhayati (JOBS (Jurnal Of Business Studies), 2025)
PT Poliplas Makmur Santosa is a plastic packaging manufacturing company that markets its products internationally. In its operations, the company still faces several challenges, such as high absenteeism, employee resignations with less than three years of service, inadequate inventory, and ineffective communication between departments. This study aimed to examine the influence of Self-Efficacy, the Physical Work Environment, and Internal Communication on Job Satisfaction among non-production employees. This study involved 70 respondents using a saturated sampling method. Data were collected using questionnaires, observations, and literature reviews, and then analyzed using SPSS version 25. The results showed that the Physical Work Environment and Internal Communication significantly influenced Job Satisfaction, while Self-Efficacy had no significant effect. The most dominant variable was Internal Communication, so the company needs to improve training, provide adequate facilities, and organize discussion forums to improve employee job satisfaction.